Plasma-Material-Interaction Research Using PISCES Linear Plasma Devices. (3rd October 2019) - Baldwin, M. J.; Doerner, R. P.; Nishijima, D.; Patino, M.; Simmonds, M. J.; Tynan, G.; Yu, J. H.; Založnik, A.
Abstract: Recent plasma-material-interaction (PMI) studies of relevance to fusion PMI science are discussed. The results are a mix of science experiments and in situ diagnostic technology development. Scientific issues addressed include the nature of He and W atom migration in the evolution of W fuzz surfaces, understanding the nature of D retention in damaged W surfaces via modeling with the tritium migration and analysis program, and an examination of synergistic effects associated with D trapping on composite Be codeposit and W substrate surfaces. In situ diagnostic developments discussed include laser-induced desorption spectroscopy for the measurement of bulk hydrogen retention and laser-induced breakdown spectroscopy for the measurement of near-surface composition.